Nanostructured Materials for Next-Generation Energy Storage and Conversion : Hydrogen Production, Storage, and Utilization - Chen, Ying-Pin; Bashir, Sajid; Liu, Jingbo Louise (Springer Berlin Heidelberg : Imprint: Springer, 2017)
Volume 1 of a 4-volume series is a concise, authoritative and an eminently readable and enjoyable experience related to hydrogen production, storage and usage for portable and stationary power. Although the major focus is on hydrogen, discussion of fossil fuels and nuclear power is also presented where appropriate. This monograph is written by recognized experts in the field, and is both timely and appropriate as this decade will see application of hydrogen as an energy carrier, for example in transportation sector. The world's reliance on fossil fuels is due to the ever growing need for energy to sustain life and on-going progress; however exploitation also brings consequences such as emission of carbon, nitrogen and sulfur dioxides into the atmosphere. The collective influence of these photochemical gases is production of acid rain and an alternation of global temperatures, leading to record high temperatures in many parts of the world. The fossil fuel is unsustainable and thus there is a critical need for alternative sustainable energy resources. One universal energy carrier is hydrogen, which is the focus of this volume. This book is suitable for those who work in the energy field as technical experts, including engineers and scientists, as well as managers, policy and decision-makers, environmentalists and consultants. Students and practitioners such as lectures, teachers, legislators and their aids in the field of energy will find this book invaluable and a practical handbook or guide in the field of sustainable energy with emphasis on hydrogen as an energy carrier.